2008
DOI: 10.2495/sdp-v3-n3-272-292
|View full text |Cite
|
Sign up to set email alerts
|

Crime prevention through environmental design in Western Australia: planning for sustainable urban futures

Abstract: Purpose: Cities as places of human habitation have multiple and interwoven impacts on the environment and upon their inhabitants. There are many defi nitions and interpretations of sustainable development and various models exist for the sustainable city, ranging from 'light green' to 'dark green'. This paper discusses the 'redesigning the city' model and investigates the extent to which crime and fear of crime are integrated within this framework and argues that crime prevention through environmental design (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…The crime dimension to sustainability has only recently been subject to widespread scrutiny (Napier et al, 1998;Vanderschueren, 1998;Du Plessis, 1999;Cozens et al, 1999;Cozens, 2002Cozens, , 2007aGlasson & Cozens, 2011) and sustainability protocols arguably do not adequately represent realistic or appropriate indicators of the levels of crime or the fear of crime (Cozens, 2007a(Cozens, , 2008a. It is argued that a sustainable urban environment is one where the inhabitants 'should not have cause for fear for their personal safety and the safety of possessions ' (Du Plessis, 1999, p. 33).…”
Section: Sustainability Crime and Cptedmentioning
confidence: 99%
See 1 more Smart Citation
“…The crime dimension to sustainability has only recently been subject to widespread scrutiny (Napier et al, 1998;Vanderschueren, 1998;Du Plessis, 1999;Cozens et al, 1999;Cozens, 2002Cozens, , 2007aGlasson & Cozens, 2011) and sustainability protocols arguably do not adequately represent realistic or appropriate indicators of the levels of crime or the fear of crime (Cozens, 2007a(Cozens, , 2008a. It is argued that a sustainable urban environment is one where the inhabitants 'should not have cause for fear for their personal safety and the safety of possessions ' (Du Plessis, 1999, p. 33).…”
Section: Sustainability Crime and Cptedmentioning
confidence: 99%
“…Investigating the urban 'stage', where (and when) crime is located, can therefore contribute much to our existing knowledge and understanding of crime and assist in the creation and maintenance of safer, vibrant and more sustainable urban communities. Indeed, there is a growing body of research that links urban sustainability with crime (Du Plessis, 1999;Cozens, 2002Cozens, , 2007aCozens, , 2008aKnights et al, 2002;Dewberry, 2003;Armitage, 2007;Glasson & Cozens, 2011). It is increasingly recognized that a sustainable community is one that is both safe and perceived by its residents to be safe from crime.…”
Section: Introductionmentioning
confidence: 99%
“…Cozens [62] claims that such issues as crime and the fear of crime are not effectively represented within most sustainability agendas and require explicit inclusion. He provides recommendations for integrating crime and the fear of crime within urban sustainability [62].…”
Section: Criteria Of a Sustainable Built Environment And The Assessmementioning
confidence: 99%
“…Viteikiene and [50], Dempsey et al [51], Lee et al [54], Charoenkit, Kumar [59], Conejos et al [60,61], Cozens [62] and others have also analyzed the criteria of safety. Cozens [62] claims that such issues as crime and the fear of crime are not effectively represented within most sustainability agendas and require explicit inclusion. He provides recommendations for integrating crime and the fear of crime within urban sustainability [62].…”
Section: Criteria Of a Sustainable Built Environment And The Assessmementioning
confidence: 99%
“…For instance, according to Ceccato and Lukyte [64], "a sustainable community shall be a place free from the fear of crime, where a feeling of security underpins a wider sense of place attachment and place attractiveness". Cozens [65] noted that "such issues as crime and the fear of crime are not effectively represented within most sustainability agendas and require explicit inclusion". Research by Zavadskas et al [30] indicated safety as the most important criterion in social dimension for assessment sustainability of Vilnius districts.…”
Section: Neighbourhood /Community Considerationsmentioning
confidence: 99%